The effect of natural products on inflammatory cytokines production and secretion - Muna Barakat; Nabeel Kashan Syed; Eliza Hasen; Shaymaa B. Abdulrazzaq; Samar Thiab; Mohammad A.A. Al-Najjar; Amin Omar; Tanzima Tarannum Lucy; A.N.M. Mamun-; Masayuki Yagi; Yoshikazu Yonei (Elsevier, 2023)
Background: The human body is regulated by the controlled production and secretion of thousands of chemicals, including polypeptides called cytokines. Cytokines play crucial roles in the immune system reaction following tissue injury and/or body invasion by infectious or non-infectious bodies. They are classified as pro and anti-inflammatory cytokines depending on many factors such as structure and function. Some cytokines mediate inflammatory reactions and contribute to several diseases, such as Rheumatoid arthritis. Very few effective treatment strategies exist to tackle these inflammatory diseases and the available strategies for treatment are also associated with several severe side effects. Although we are in the scientific innovations and medical advancements era, natural compounds are still competing with modern artificial drugs and performing well to effectively treat many diseases without causing side effects. The main purpose of this review is to discuss the effect of some natural compounds on inflammatory cytokine production and elaborate their mode of action further based on already available and recently published literature. Methods: We have reviewed a selected number of natural compounds (Echinacea, Curcumin, Genistein, Eugenol, 6-Gingerol, Thymoquinone, Allicin, Quercetin, Emodin and Parthenolide) that have shown pronounced effects on cytokine production and secretion in several physiological conditions. Findings and Conclusion: Immune cells produce multiple pro-inflammatory and anti-inflammatory cytokines that could be regulated accurately and effectively by using some natural compounds that can block the intracellular machinery and thus reduce cytokine production and secretion. This offers an intriguing background for grasping how these products conduct their activity at a cellular level and sheds light on other natural products to examine efficiency in the same aspect.